KINERJA WAITERS LINGGA RESTAURANT DI HOTEL LADIVA PEKANBARU - Della Rahmi Pratiwi; Andi M. Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this research is to know the performance of Lingga Restaurant waiters at Hotel Ladiva Pekanbaru, to know what factors affect the performance of waiters Lingga Restaurant, and efforts in improving the performance of waiters.This research uses descriptive quantitative method to analyze the problem. The sample used was 30 respondents and the data obtained through questionnaires, observations, and interviews. By using Likert scale as a measuring instrument to determine the length of the interval.Based on the results of research, the performance of waiters at Lingga Restaurant at Hotel Ladiva Pekanbaru consisting of six indicators are: ability, motivation, attitude, situatation, knowledge, skill. The performance of the most unfortunate waiters is on the ability of waiters.Keywords: Performance, Waiters, Restaurant